Pengaruh Edukasi Latihan Back Strengthening dan Latihan Mobilitas untuk Koreksi Postur Mahasiswa dengan Kebiasaan Duduk Prolonged Sitting - Jhon Roby Purba; Theresia Anggriani H; Tuty Swarni Sinaga (Lembaga Pengembangan Kinerja Dosen, 2024)
Prolonged sitting habits among university students increase the risk of postural abnormalities such as forward head posture and rounded shoulders, which may lead to low back pain and reduced quality of life. The lack of postural awareness and limited preventive interventions on campuses are pressing issues to address.This study aimed to analyze the effectiveness of an educational and corrective exercise program consisting of back strengthening and mobility exercises on improving student posture. This study applied a quasi-experimental design with a one-group pretest-posttest approach. A total of 30 students with ≥4 hours/day of sitting participated in a 4-week intervention program (3 sessions per week). Measured parameters included Forward Head Posture (FHP), Rounded Shoulder Posture (RSP), and the Postural Awareness Scale (PAS). Data were analyzed using paired t-tests. The results indicated significant reductions in FHP (mean decrease of 2.30 cm) and RSP (mean decrease of 7.2°), along with a significant increase in PAS scores (mean increase of 15.49 points) with p < 0.01. The program effectively improved both postural alignment and awareness. A combination of postural education and corrective exercises is effective in improving student posture. This intervention is recommended as a preventive and promotive approach to musculoskeletal health in university settings.